Screening and Management for Dyslipidemia in Korean Children and Adolescents - Jong Seo Yoon; Il Tae Hwang (The Ewha Medical Journal)
Cardiovascular disease (CVD) is the most common cause of death worldwide, and dyslipidemia is a major risk factor. Atherosclerosis can begin in childhood and continue into adulthood, thereby contributing to CVD development. Obesity is the most common cause of dyslipidemia, and the prevalence of childhood obesity and dyslipidemia is increasing worldwide, making it a public health concern. As clinical evidence has accumulated, guidelines for dyslipidemia in children have been continuously revised since 1992. The limitations of screening tests for individuals with a family history of dyslipidemia emphasize the necessity of universal screening, and non-HDL cholesterol assessment is recommended as a screening test for dyslipidemia in children. The guidelines for dyslipidemia in Korean children and adolescents published in 2017 recommend that non-HDL cholesterol screening tests be performed in non-fasting conditions at 9–11 years and 17–21 years of age. The main purpose of this article is to describe the history and rationale of lipid screening recommendations in children and adolescents and to review the currently recommended screening methods and treatments for dyslipidemia. (Ewha Med J 2022;45(3):e4)